Decrease of Preoperative Serum Albumin-to-Globulin Ratio as a Prognostic Indicator after Radical Cystectomy in Patients with Urothelial Bladder Cancer: Albumin-to-globulin ratio and bladder cancer - Oh, Jeong Seock; Park, Dong Jin; Byeon, Kyeong-Hyeon; Ha, Yun-Sok; Kim, Tae-Hwan; Yoo, Eun Sang; Kwon, Tae Gyun; Kim, Hyun Tae (Urology Journal, 2021)
Purpose: This study aims to evaluate whether preoperative serum albumin-to-globulin ratio (AGR) could predict the prognosis of patients with urothelial bladder cancer (UBC) after radical cystectomy (RC). Materials and Methods: A total of 176 patients with UBC who underwent RC in a tertiary hospital between 2008 and 2019 were retrospectively analyzed. The AGR was calculated as albumin/(total protein − albumin). In addition, the AGR was divided into two groups for the time-dependent receiver operating characteristic curve (ROC) analysis. Survival was estimated using the Kaplan–Meier analysis and compared using the log-rank test. Cox proportional- hazards models were used for multivariate survival analysis. Results: The best cutoff AGR value for metastasis prediction was 1.32 based on the ROC curve analysis. Patients who had lower pretreatment AGR (<1.32) values composed the low-AGR group (n = 57; 32.4%). On the other hand, the remaining patients (n = 119; 67.6%) composed the high-AGR group. The patients in the low-AGR group had more advanced stage tumors compared with the patients in the high-AGR group. The Kaplan–Meier curves revealed that the patients in the low-AGR group had significantly lower rates of metastasis-free survival (MFS) and cancer-specific survival (CSS). The multivariate Cox regression analysis showed that preoperative AGR was an independent prognostic factor for MFS and CSS. Conclusion: In this single-institution retrospective study, lower preoperative AGR values demonstrated a poor prognostic effect on MFS and CSS in patients with UBC who underwent RC.